Ethylene response factors regulate expression of HbSUT3, the sucrose influx carrier in laticifers of Hevea brasiliensis. (8th February 2021) - Zhang, Yi; Xin, Lusheng; Pirrello, Julien; Fang, Yongjun; Yang, Jianghua; Qi, Jiyan; Montoro, Pascal; Tang, Chaorong
Abstract: Natural rubber is an important industrial raw material and is commercially produced by rubber trees ( Hevea brasiliensis ). The sucrose transporter HbSUT3 plays an essential role in rubber production. Its expression in latex (cytoplasm of rubber-producing laticifers) is induced by bark treatment with Ethrel, an ethylene releaser, and the inducing effect correlates well with Ethrel-stimulated rubber yield increase. However, the mechanisms of ethylene induction on HbSUT3 expression are not known. Here, five Ethylene Response Factor ( ERF ) genes were identified from the cDNA library of Hevea latex by yeast one-hybrid screening with the promoter of HbSUT3 gene as bait. As revealed in a tobacco ( Nicotiana tabacum ) protoplast transient expression system, these HbERFs were mainly localized in the nucleus and four of them exhibited apparent transactivation activity. Of the five HbERF genes, HbERF-IXc4 was the most frequently screened in yeast one-hybrid, accounting for 65% of the ERF clones obtained. Moreover, among the five HbERF s, HbERF-IXc4 showed the strongest transactivation capacity when expressed in tobacco protoplast, the highest transcript abundance in latex and a close expressional correlation with its target gene, HbSUT3, in response to the Ethrel treatment. Taken together, our results indicate that ERFs, especially HbERF-IXc4, are critically involved in the activation of HbSUT3 expression in latex after Ethrel treatment on Hevea bark, and thus the stimulated latex yield.